Arctic - Burton, Robert (Belitha Press London, 1994)
Part of a series, which brings to children an appreciation of the way animals and their families really live, this book is about homes in the Arctic. It shows how animals without human skills are equally imaginative when it comes to finding comfortable and safe places to live .